2005
DOI: 10.1063/1.1852579
|View full text |Cite
|
Sign up to set email alerts
|

Commutator errors in the filtering approach to large-eddy simulation

Abstract: We analyze the large-eddy equations that are obtained from the application of a spatially nonuniform filter to the Navier-Stokes equations. Next to the well-known turbulent stress tensor a second group of subgrid terms arises; the so-called commutator errors. These additional subgrid terms emerge in the large-eddy equations solely as a consequence of the nonuniformity of the filter. We compare the magnitude of the divergence of the turbulent stress tensor with that of the commutator errors and pay attention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…We notice that the filter corresponding to a higher-order spatial discretization is itself a higher-order filter; with increasing order, the Fourier transform of the kernel is seen to stay closer to the identity operator for a wider range of wave numbers. 21,22,24 Each discretization method gives rise to a particular damping of the amplitude of individual modes, which induces a specific dynamic contribution in an actual large-eddy simulation based on this method. The role of the total filter is discussed further in, e.g., Refs.…”
Section: -6 B J Geurts and F Van Der Bosmentioning
confidence: 99%
See 1 more Smart Citation
“…We notice that the filter corresponding to a higher-order spatial discretization is itself a higher-order filter; with increasing order, the Fourier transform of the kernel is seen to stay closer to the identity operator for a wider range of wave numbers. 21,22,24 Each discretization method gives rise to a particular damping of the amplitude of individual modes, which induces a specific dynamic contribution in an actual large-eddy simulation based on this method. The role of the total filter is discussed further in, e.g., Refs.…”
Section: -6 B J Geurts and F Van Der Bosmentioning
confidence: 99%
“…3 A filter kernel is characterized by an externally specified length scale parameter , which defines the effective filter width ⌬; e.g., as 22 1…”
Section: Decomposition Of the Numerical Turbulent Stress Tensormentioning
confidence: 99%
“…Most studies of the commutator error that were reported in literature relied on an analytical evaluation of the commutator error 5,6,9,12 or on a priori investigations using DNS data. 7 In this paper an explicit Lagrangian interpretation of the dynamics of commutator errors is provided which directly suggests a corresponding SFS model. We examine the effect of commutator errors on the transport of resolved kinetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…We will formulate the explicit Lagrangian commutator-error model and test it against other commutator-error models ͑CE models͒ that are based on similarity assumptions instead. [6][7][8] The type of nonuniform filter in the definition of the commutator error explicitly affects the type of dynamic contributions of these terms. We will investigate both the commonly used symmetric filters as well as skewed filters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation